Sistem Pendukung Keputusan Pemilihan Sekolah SMK Swasta Penerima Dana Bantuan Menerapkan Metode Simple Additive Weighting (SAW) - Jeperson Hutahaean; Muliati Badaruddin (STMIK Budi Darma, 2020)
Education is a gate to start the formation of a developed and one-nation country and education is also a gateway to the success of the nation's children, education is something that must be owned by every child and even must be owned by every individual, but there are still many children of the nation who cannot obtain education due to the high cost of education, many donors and volunteers who help unconditionally make a movement of assistance to the level of education, assistance is not only from the government but other there is assistance from outside parties provided to the school aims to provide free educational scholarships at the SMK level (School Secondary Vocational) in private schools, the donors choose to provide funding for vocational level because it is considered Minimum education is at the level of vocational / high school and its level is equivalent, so many Private Schools in the City of Medan so that a decision support system is needed to avoid mistakes in the selection of private high school schools receiving scholarship assistance funds, in this study using the SAW (Simple Additive Weighting) method